PERFECT RHYTHMIC TILINGS. - Davalan, Jean Paul (Perspectives of New Music)
The article presents the computation for the perfect rhythmic tilings. It mentions that the perfect rhythmic tiling is computed by a computer program. It offers that references to similar work done by researchers Tom Johnson, C. J. Bouwkamp and N. J. A. Sloane. It adds that classical rhythmic canon survey and algorithms.